Unavoidable conflict between massive gravity models and massive topological terms - Accioly, A.; Dias, M. (World Scientific Publ Co Pte Ltd, 2004)
Massive gravity models in (2 + 1) dimensions, such as those obtained by adding to Einstein's gravity the usual Fierz-Pauli, or the more complicated Ricci scalar squared (R-2), terms, are tree level unitary. Interesting enough these seemingly harmless systems have their unitarity spoiled when they are augmented by a Chern-Simons term. Furthermore, if the massive topological term is added to R + R-munu(2) gravity, or to R + R-munu(2), + R-2 gravity (higher-derivative gravity), which are nonunitary at the tree level, the resulting models remain nonunitary. Therefore, unlike the common belief, as well as the claims in the literature, the coexistence between three-dimensional massive gravity models and massive topological terms is conflicting.
Keywords: massive gravity models; topological terms; tree unitarity